CHATGPT AND STUDENTS' CRITICAL THINKING SKILLS: A CORRELATIONAL ANALYSIS ON COMMUNICATION SCIENCE STUDENTS AT SINGAPERBANGSA KARAWANG UNIVERSITY - Erina Nur Rohmah; Weni A. Arindawati; Nurkinan Nurkinan (Journal of Research in Social Science and Humanities, 2025)
Advances in artificial intelligence (AI) technology such as Chat GPT have had a major impact on the way students access and manage information in an academic environment. Despite its efficiency benefits, concerns have been raised about the potential reduction of critical thinking skills due to the tendency to rely on instant answers. This study aims to evaluate the extent to which the use of Chat GPT is related to the critical thinking skills of undergraduate students of Communication Studies Program at Singaperbangsa University of Karawang. The quantitative research method was used with the Uses and Effect theory as the foundation, and data was obtained from 126 students through the distribution of questionnaires. Analysis using simple linear regression test resulted in a significance value of 0.001 0.05, so it can be concluded that there is a statistically significant influence between the use of Chat GPT and students' critical thinking skills. The findings show a significant positive relationship between the variables studied, with a significance value of 0.001 (p 0.05) with the results of the calculation of the correlation coefficient of 0.631, it can be concluded that the level of relationship between the two main variables in this study, namely the utilization of Chat GPT and students' critical thinking skills, is included in the strong category.